2016
DOI: 10.1007/s10967-016-4898-y
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of uranium(VI) from aqueous solution using a novel magnetic hydrothermal cross-linking chitosan

Abstract: The magnetic hydrothermal cross-linking chitosan (HCC-Fe 3 O 4 ) was prepared by hydrothermal carbonization and was characterized by FT-IR, X-ray diffraction and scanning electron microscopy. The as-prepared HCC-Fe 3 O 4 was used as adsorbent to remove uranium(VI) as functions of contact time, pH, temperature and initial uranium(VI) concentration batch wise. The results indicated that the magnetic HCC-Fe 3 O 4 was favorate for solid-liquid separation and the maximum uranium(VI) adsorption capacity was 263.1 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…It is a strategic resource in the nuclear industry and, as a result, uranium plays an important and irreplaceable role in the production of nuclear energy [ 9 ]. However, it is chemically and radioactively toxic, and has a long half-life with a high radiological and biological toxicity, causing irreversible damage in humans and the environmental ecosystem [ 10 , 11 ]. Inevitably, uranium can escape into the environment in the mining processes, nuclear research, and weapons manufacture, as well as due to improper nuclear waste management, and nuclear safety accidents [ 9 ].…”
Section: Synthetic Routes and Characterizationsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a strategic resource in the nuclear industry and, as a result, uranium plays an important and irreplaceable role in the production of nuclear energy [ 9 ]. However, it is chemically and radioactively toxic, and has a long half-life with a high radiological and biological toxicity, causing irreversible damage in humans and the environmental ecosystem [ 10 , 11 ]. Inevitably, uranium can escape into the environment in the mining processes, nuclear research, and weapons manufacture, as well as due to improper nuclear waste management, and nuclear safety accidents [ 9 ].…”
Section: Synthetic Routes and Characterizationsmentioning
confidence: 99%
“…The magnetic properties of HCC-Fe 3 O 4 were proved with the use of a magnet. The results showed that HCC-Fe 3 O 4 dispersed in a water solution could be easily separated from water with a magnet, in contrast with HCC/water, which was still cloudy [ 10 ].…”
Section: Synthetic Routes and Characterizationsmentioning
confidence: 99%
“…Such magnetic fields, however, cannot be used to regenerate the IAs since their ion adsorption capacities depend on ion binding units functionalized on the surface of the magnetic nanoparticles. high-concentration chemical solutions of hydrochloric acid (HCl), 33−35 sodium hydroxide (NaOH), 36,37 sulfuric acid (H 2 SO 4 ), 38,39 sodium chloride (NaCl), 40,41 ethylenediaminetetraacetic acid (EDTA), 42,43 sodium carbonate (Na 2 CO 3 ), 44,45 and nitric acid (HNO 3 ), 46 and mixed solutions of HCl− ethanol 32 and HCl−thiourea 47 as eluents have been widely used to desorb the IAs. 48,49 Although such chemical-dependent regeneration facilitates good reusability of the IAs, these chemical-intensive regeneration processes are likely to lead to secondary environmental pollution.…”
Section: Introductionmentioning
confidence: 99%
“…Such magnetic fields, however, cannot be used to regenerate the IAs since their ion adsorption capacities depend on ion binding units functionalized on the surface of the magnetic nanoparticles. To regenerate the IAs, high-concentration chemical solutions of hydrochloric acid (HCl), sodium hydroxide (NaOH), , sulfuric acid (H 2 SO 4 ), , sodium chloride (NaCl), , ethylenediaminetetraacetic acid (EDTA), , sodium carbonate (Na 2 CO 3 ), , and nitric acid (HNO 3 ), and mixed solutions of HCl–ethanol and HCl–thiourea as eluents have been widely used to desorb the IAs. , Although such chemical-dependent regeneration facilitates good reusability of the IAs, these chemical-intensive regeneration processes are likely to lead to secondary environmental pollution . In the attempt to minimize the use of chemicals in the regeneration processes, a number of functionally responsive molecules have been adopted to synthesize a series of SRIAs that exhibit responsive characteristics to various physical stimuli (Figure d), such as thermal-responsive poly­( N , N ′-dimethylvinyl-benzylamine) (PDMVBA) and poly­( N -isopropylacrylamide) , (PNIPAM); CO 2 -responsive poly­(2-dimethylaminoethyl methacrylate) (PDMAEMA) and poly N , N -diethylacrylamide (PDEA), pH-responsive carboxymethyl cellulose , (CMC), polyitaconic acid, poly­(acrylic acid) (PAA), polyamidoxime, , polyaniline, , and poly­(allylsulfonic acid) (PASA); light-responsive coumarin, spiropyran (SP), and azobenzene (AZO) molecules; ion-responsive crown ethers ( i.e ., acryloylamidobenzo-18-crown-6 (AmB18C6) and dibenzo-14-crown-4 (DB14C4)); and voltage-responsive polypyrrole, , and GO composites …”
Section: Introductionmentioning
confidence: 99%